A trust-based virtual collaborative environment - Kamel, M.; Laborde, R.; Barrère, F.; Benzekri, A. (Journal of Digital Information Management, 2008)
The concept of Virtual Organisation (VO) is a natural outcome of networks evolution and collaborative work tools growth. In the VIVACE and TSCP projects, we have studied the different issues when setting VOs up. In this paper, we expose requirements and characteristics of VOs through a use case, which was proposed by these two consortiums. Then, we present a secured collaborative environment, which combines attribute based access control models, privilege management infrastructure and identity federation, we have deployed to deal with VO security constraints. This architecture allows organisations to externalise processes such as authenticating remote users to their partners (the users' home organisations). The establishment of such a decentralised management solution implies these organisations to be sufficiently mature to deal with such delegated tasks. We consider the maturity of the security practices deployed within each organisation to choose the trustee organisations between the potential partners. We provide a tool that helps organisations to evaluate their maturity.
Keywords: ABAC; Identity federation; ISO/IEC 27000; Maturity level; PMI; Virtual Organisation